Development of digital-based return board table tennis learning media - Gumilar, Agus; Negara, Jajat Darajat Kusumah; Nuryadi, Nuryadi; Firmansyah, Helmy; Mudjihartono, Mudjihartono; Hambali, Burhan; Purnomo, Eko (Department of Coaching, Faculty of Sports Science, Universitas Negeri Padang, Indonesia, 2024)
Problems: Technology is very important in sports, both on and off the field. The use of technology-based applications in sports is very important in supporting athlete training systems and producing accurate data for measuring sports performance. Purpose: This research involves developing a conventional return board into a digital-based return board. Digital return board media can be used as a learning, evaluation, and coaching medium in table tennis games. The research carried out is research and development. Methods: Research and development (R&D) research is essentially an effort to develop a prototype of a research-based tool or device, namely the digitization of conventional return boards. After the media return board is produced, the next stage is to carry out analysis by validating the digital return board by experts. Results: The research used three experts, namely practitioner experts represented by test and measurement course lecturers, media experts who were experts in the field of computer programming, practitioners who were trainers, and professional athletes. Each expert will analyze each trial from a small scale to a large scale. The three experts gave an average of the test results on a scale of 80% after going through three stages, so this return board was deemed to meet the requirements to be used as a training and learning medium in table tennis games. Conclusion: It is hoped that the results of this research can become a technological medium in table tennis playing activities, especially in improving the performance of table tennis players based on accurate data.